Macular thickness and macular volume measurements using spectral domain optical coherence tomography in normal Nepalese eyes - Pokharel A (Dove Medical Press, 2016)
Amrit Pokharel,1 Gauri Shankar Shrestha,2 Jyoti Baba Shrestha2 1Department of Ophthalmology, Kathmandu Medical College Teaching Hospital, 2B P Koirala Lions Centre for Ophthalmic Studies, Institute of Medicine, Kathmandu, Nepal Purpose: To record the normative values for macular thickness and macular volume in normal Nepalese eyes. Methods: In all, 126 eyes of 63 emmetropic subjects (mean age: 21.17±6.76 years; range: 10–37 years) were assessed for macular thickness and macular volume, using spectral domain-optical coherence tomography over 6×6 mm2 in the posterior pole. A fast macular thickness protocol was employed. Statistics such as the mean, median, standard deviation, percentiles, and range were used, while a P-value was set at 0.05 to test significance. Results: Average macular thickness and total macular volume were larger in males compared to females. With each year of increasing age, these variables decreased by 0.556 µm and 0.0156 mm3 for average macular thickness and total macular volume, respectively. The macular thickness was greatest in the inner superior section and lowest at the center of the fovea. The volume was greatest in the outer nasal section and thinnest in the fovea. The central subfield thickness (r=-0.243, P=0.055) and foveal volume (r=0.216, P=0.09) did not correlate with age. Conclusion: Males and females differ significantly with regard to macular thickness and macular volume measurements. Reports by other studies that the increase in axial length reduced thickness and volume, were negated by this study which found a positive correlation among axial length, thickness, and volume. Keywords: macular thickness, macular volume, optical coherence tomography, Nepal